Dental Care Utilization for Examination and Regional Deprivation - Cheol-Sin Kim; Sun-Young Han; Seung Eun Lee; Jeong-Hee Kang; Chul-Woung Kim (Korean Society for Preventive Medicine, 2015)
Objectives: Receiving proper dental care plays a significant role in maintaining good oral health. We investigated the relationship between regional deprivation and dental care utilization. Methods: Multilevel logistic regression was used to identify the relationship between the regional deprivation level and dental care utilization purpose, adjusting for individual-level variables, in adults aged 19+ in the 2008 Korean Community Health Survey (n=220 258). Results: Among Korean adults, 12.8% used dental care to undergo examination and 21.0% visited a dentist for other reasons. In the final model, regional deprivation level was associated with significant variations in dental care utilization for examination (p<0.001). However, this relationship was not shown with dental care utilization for other reasons in the final model. Conclusions: This study's findings suggest that policy interventions should be considered to reduce regional variations in rates of dental care utilization for examination.